Longitudinal Socio-Emotional Learning Intervention for Autism via Smartglasses: Qualitative School Teacher Descriptions of Practicality, Usability, and Efficacy in General and Special Education Classroom Settings - Neha U. Keshav; Arshya Vahabzadeh; Rafiq Abdus-Sabur; Krystal Huey; Joseph P. Salisbury; Runpeng Liu; Ned Sahin (MDPI AG, 2018)
There is considerable demand for special education services for the over half a million students with autism in the United States. While assistive technology may augment educational services, its implementation is often prevented by a number of practical and attitudinal barriers. These barriers are especially pertinent for the newest and thus least familiar digital systems, such as computerized smartglasses loaded with specialized software modules. Computerized smartglasses are a technology that has already been shown to have an ability to deliver educational interventions through augmented reality. With this in mind, we sought to understand how school educators received and assessed the practicality of a smartglasses-based educational intervention in a single-subject study. The intervention was designed to aid with attention and social educational learning in autism. The intervention was delivered twice a day during a two-week study on a 13-year-old student with autism who was attending a mainstream middle school in Massachusetts. Three different school educators delivered the intervention: the student’s general education teacher, special education teacher, and paraprofessional. Educators recorded their attitudes, the practicality of the technology, and its impact on the student and their classroom through the use of a digital log and a series of in-person interviews. Overall, the school educators experienced a positive view of the smartglasses. The smartglasses intervention was found to be logistically practical to implement, easily usable by both the educator and student, and not time-consuming to learn or implement. Educators also identified the experience as being fun for the student, and felt that the student demonstrated improvement in his verbal and non-verbal skills. There were no adverse effects on the other students or the classroom, and the technology did not result in a distraction. These findings suggest that social skills interventions delivered by smartglasses may be practical, useful, and may lead to improvements in social communication skills. Further research on smartglasses may help to clarify the future role for augmenting special education in students with autism.